2019
DOI: 10.2118/195687-pa
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of the Viscoelastic Effects During Polymer Flooding: A Critical Review

Abstract: Summary Since the late 1960s, several enhanced–oil–recovery (EOR) researchers have developed various continuum and pore–scale viscoelastic models for quantifying the altered injectivity and incremental oil recovery because of the polymer's viscoelastic effects. In this paper, limitations in each of the continuum and pore–scale models are discussed. The critiques are made on the basis of the contradicting literature. Most of the earlier models rely on the exclusive use of the Debor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(45 citation statements)
references
References 6 publications
0
45
0
Order By: Relevance
“…Likewise, as HPAM polymer concentrations increase or the brine salinity decreases, the shear-thickening flow behavior becomes more prominent [17]. The complexities of the non-Newtonian in-situ rheology displayed by polymer solutions have driven the development of several models to understand the flow of polymer solutions through porous media; for further details, readers are referred to [111,117,118] and the references therein. Recently, Daripa and Dutta developed a hybrid numerical method for an immiscible two-phase, multicomponent, incompressible flow in porous media, as is the case of polymer flooding [118].…”
Section: Flow Behavior Of Polymers Through Porous Mediamentioning
confidence: 99%
“…Likewise, as HPAM polymer concentrations increase or the brine salinity decreases, the shear-thickening flow behavior becomes more prominent [17]. The complexities of the non-Newtonian in-situ rheology displayed by polymer solutions have driven the development of several models to understand the flow of polymer solutions through porous media; for further details, readers are referred to [111,117,118] and the references therein. Recently, Daripa and Dutta developed a hybrid numerical method for an immiscible two-phase, multicomponent, incompressible flow in porous media, as is the case of polymer flooding [118].…”
Section: Flow Behavior Of Polymers Through Porous Mediamentioning
confidence: 99%
“…Experimental studies have reported that polymer viscoelasticity may improve oil recovery [ 30 , 31 , 32 ]. Similarly, the synergies of modified water-flood with polymer flood are expected to produce more oil as compared to single EOR technique [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Shear-thickening behavior can be observed after the polymer flow has reached the second critical shear rate as shown in Figure 5 . A remarkable observation that can be made from this plot is that shear thickening is only encountered in porous media during polymer flooding and not in rotational rheometer measurements [ 8 , 20 , 26 , 27 , 63 , 65 , 66 , 67 , 68 ]. It is believed that the missing shear thickening is the result of the missing flow motion, since the viscosity increase is commonly explained with a distinctive stretching of the polymer molecule [ 27 , 69 ].…”
Section: Viscoelasticity In Enhanced Oil Recoverymentioning
confidence: 99%